I speak for myself American women on being Muslim - Ebrahimji, Maria M.; Suratwala, Zahra T. (Ashland, Or. White Cloud Press, 2011)
Forty women under age forty share what it has been like to have been born and raised in the United States as a Muslim, examining the dichotomy between Islamic and Western values, and discussing stereotypes, the events of 9/11, and other related topics.
505 0 Hill diaries / Yusra Tekbali -- Pieces / Rima Z. Kharuf -- Roots / Fatemeh Fakhraie -- Half and half / Nousheen Yousuf-Sadiq -- In search of Fatima and Taqwa / Maria M. Ebrahimji -- The muslim feminist / Hebah Ahmed -- Conquering veils : gender and Islams / Asma T. Uddin -- Unwelcome change / Mona Rajab -- The university of life / Jameelah Xochitl Medina -- Seeking the present / Zahra T. Suratwala -- Sporting faith / Dewnya Bakri-Bazzi -- Crossroads / Hadia Mubarak -- Secularizing my graduation / Arshiya Saiyed -- A headscarf away from television / Mariam Sobh -- What a day / Sarah Pashtoon Azad -- Itchy feet / Arshia Khan -- Moment of truth / Ruqayya Raheem Gibson -- The writings on the wall / Maytha Alhassen -- There and back again : a spiritual journey / Marryam Abdl- Haleem -- In between two worlds / Elham Khatami -- Connections / Samaa R. Abdurraqib -- Hyphenated identity / Naheed Hamid -- My journey to Islam / Saliqa A. Khan -- Hello my name is / Amira Choueiki -- Ready to wear / Nyla Hashmi -- Learning tolerance / Sevim Sabriye Kalyoncu -- A William and Mary Ramadan / Ayah H. Ibrahim -- Soul baring and barrier breaking / Nafees Asiya Syed -- Bursting out of a bubble / Sama Wareh -- A sister in humanity / Zahra Nasiruddin Jamal -- "Who am I to you?" / Amany S. Ezeldin -- Truth is not always self-evident / Rabea Chaudhry -- Shock and awe / Zainab Alwan -- A search for peace / Ala'a Wafa -- Army of one / Maryam Habib Khan -- 2008 Campaign / Rashida Tlaib -- Dual identities / Reem Odeh -- Creating sarah / Sarah Kajani -- The voice from within / Souheila Al-Jadda -- Lines of bad grammar / Kameelah Janan Rasheed.
Keywords: Muslim women -- United States; Muslim women -- Religious life -- United States; Women in Islam -- United States